Analysis of Factors Related to Safety Riding in Employees of the Karangmalang Health Center in Semarang City in 2025. - Azhar Tegar; Supriono Asfawi (Journal Occupational Health Hygiene and Safety, 2026)
Traffic accidents are still a public health problem, especially for motorcycle users in the productive age group. This study aims to analyze factors related to safety riding behavior in employees of the Karangmalang Health Center in Semarang City. This study is a quantitative analysis with a cross-sectional design on 45 respondents who were taken in total sampling. Independent variables include age, working period, use of PPE, road environmental conditions, and family support, while dependent variables are safety riding behavior. Data were collected using a questionnaire and analyzed with a Spearman Rank test at α < 0.05. The results showed that 53.3% of respondents had good safety riding behavior. There was a significant association between age (p = 0.027; r = -0.329), road environmental conditions (p = 0.017; r = 0.353), and family support (p < 0.001; r = 0.542) and safety riding behavior, while working time (p = 0.560) and PPE use (p = 0.089) were not significantly related. The conclusion of this study is that age, road environmental conditions, and family support are related to safety riding behavior, while working period and PPE use are not related, so it is recommended to improve driving safety education, strengthen family support, and improve road infrastructure to support employee work safety.